This identities are known as Pythagorean identities because this can be represented and solved using the pythagoras theorem. Let's remind the theorem:
![A^2+B^2=C^2](https://img.qammunity.org/2023/formulas/mathematics/college/gtt065a2nkpkxiist2nyjj0kcunysg5k1b.png)
Now, we also should know that the trigonometric functions can be written using the sides of a triangle. For the tangent and secant, we know:
![\begin{gathered} \tan x=(B)/(A) \\ \sec x=(C)/(A) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xvuwypq9aofgtuleak4ohadtxdmg7htub7.png)
In the next step I will substitute this identities to the given equation:
![\begin{gathered} -\tan ^2x+\sec ^2x=1 \\ -((B)/(A))^2+((C)/(A))^2=1 \\ -(B^2)/(A^2)+(C^2)/(A^2)=1 \\ (C^2-B^2)/(A^2)=1 \\ C^2-B^2=A^2 \\ C^2=A^2+B^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3y2y12fyag1ratahq9ghotxs314b16gn0g.png)
Which satisfy the Pythagoras Theorem.